Drosophila as a Model for Infectious Diseases - Harnish, J. Michael; Link, Nichole; Yamamoto, Shinya (International journal of molecular sciences, 2021)
The fruit fly, Drosophila melanogaster, has been used to understand fundamental principles of genetics and biology for over a century. Drosophila is now also considered an essential tool to study mechanisms underlying numerous human genetic diseases. In this review, we will discuss how flies can be used to deepen our knowledge of infectious disease mechanisms in vivo. Flies make effective and applicable models for studying host-pathogen interactions thanks to their highly conserved innate immune systems and cellular processes commonly hijacked by pathogens. Drosophila researchers also possess the most powerful, rapid, and versatile tools for genetic manipulation in multicellular organisms. This allows for robust experiments in which specific pathogenic proteins can be expressed either one at a time or in conjunction with each other to dissect the molecular functions of each virulent factor in a cell-type-specific manner. Well documented phenotypes allow large genetic and pharmacological screens to be performed with relative ease using huge collections of mutant and transgenic strains that are publicly available. These factors combine to make Drosophila a powerful tool for dissecting out host-pathogen interactions as well as a tool to better understand how we can treat infectious diseases that pose risks to public health, including COVID-19, caused by SARS-CoV-2.